2018
DOI: 10.1111/1759-7714.12780
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term postoperative complications and prognostic factors in patients with adenocarcinoma of the esophagogastric junction

Abstract: BackgroundThe study was conducted to investigate the short‐term complications and prognostic factors in patients with esophagogastric junction adenocarcinoma (EGJA).MethodsThis retrospective study included 110 EGJA patients who underwent surgery from January 2010 to November 2012 at The First Affiliated Hospital of BengBu Medical College. The overall survival and short‐term complications were analyzed according to the patients’ clinical characteristics.ResultsThe incidence of postoperative cardiopulmonary comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the multivariable model on the pain dimension, older age (> 60 years) was associated with a higher risk of death at 1 year. Previous studies have identified age, pathological T stage, clinical lymph node involvement and treatment modality (surgery versus definitive chemoradiotherapy) as predictive factors of death in esophageal cancer [30][31]. The study by Tamagawa et al showed that the development of postoperative pneumonia was a risk factor for decreased 5-year OS in patients who underwent curative surgery for esophageal cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the multivariable model on the pain dimension, older age (> 60 years) was associated with a higher risk of death at 1 year. Previous studies have identified age, pathological T stage, clinical lymph node involvement and treatment modality (surgery versus definitive chemoradiotherapy) as predictive factors of death in esophageal cancer [30][31]. The study by Tamagawa et al showed that the development of postoperative pneumonia was a risk factor for decreased 5-year OS in patients who underwent curative surgery for esophageal cancer [32].…”
Section: Discussionmentioning
confidence: 99%